First-principles calculation of ideal-gas thermodynamic properties of long-chain molecules by R1SM approach-Application to n-alkanes - Štejfa, Vojtěch; Fulem, Michal; Růžička, Květoslav (The Journal of chemical physics, 2019)
First-principles calculations, coupled with statistical thermodynamics, can provide ideal-gas thermodynamic properties but get complicated and less reliable with an increasing number of conformers. An approach designed for calculation of ideal-gas thermodynamic properties of long-chain molecules, R1SM, and its simplified version, sR1SM, is tested in this work by calculation of ideal-gas heat capacities and entropies for a homologous series of n-alkanes up to n-tetradecane. The R1SM approach incorporates the rigid rotor-harmonic oscillator approximation in combination with a correction for internal rotations of methyl tops using the one-dimensional hindered rotor scheme and the mixing model accounting for the population of conformers based on the Boltzmann distribution. The R1SM approach is applicable for compounds with up to hundreds of conformers, while the simplified sR1SM approach can be used for molecules with up to 105 conformers when coupled with rules for enumeration of stable conformers and estimation scheme for their energies. The obtained results for n-alkanes are compared with experimental values and previously employed computational schemes. As the conformational behavior and conformer energies are inherent parts of the proposed approaches, a thorough conformational study of n-alkanes is performed and compared with experiments and the Tasi rules for enumeration of n-alkane conformers. Finally, the standard uncertainty of the R1SM-calculated ideal-gas thermodynamic properties is estimated based on the error propagation from the used input quantities and approximations as well as on comparison to experimental values and amounts to less than 1% for both ideal-gas heat capacity and standard ideal-gas entropy.